Increase in assisted suicide in Switzerland: did the socioeconomic predictors change? Results from the Swiss National Cohort - Marcel Zwahlen; Nicole Steck; Christoph Junker (BMJ Open)
Objective To determine whether the strong increase in assisted suicides in Switzerland since 2008 is linked to a shift in the socioeconomic factors associated with assisted suicide and its related diagnoses.Methods In a population-based longitudinal study, we investigated assisted suicides in Switzerland over the period 2003–2014. Two groups of younger (25–64 years) and older (65–94 years) persons were analysed separately and compared. We calculated crude rates and used Cox proportional hazard and logistic regression models to examine associations of assisted dying with gender, marital status, education, religion, neighbourhood socioeconomic status and other variables, and investigated trends over time.Results We identified 3941 assisted suicides among 6 237 997 Swiss residents, 80% of which occurred in the older age group. Crude rates of assisted suicide more than tripled during the study period from 3.60 to 11.21 per 100 000 person-years; the increase was more pronounced in the older age group. Cancer was the most common underlying diagnosis (41.8%), but the percentage dying assisted was highest among patients with diseases of the nervous system (5.25% in the younger and 1.23% in the older age group). The factors associated with assisted suicide did not change during the study period. Female gender, higher education, having no religious affiliation, no children and a Swiss passport, living in a neighbourhood with a higher socioeconomic index and living in the French-speaking part of Switzerland were associated with a higher rate.Conclusions The study results do not indicate any shift in socioeconomic factors associated with assisted suicide, but a more pronounced increase in incidence among the elderly.